2021
DOI: 10.3177/jnsv.67.68
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Vitamin D<sub>3</sub> Therapy in Patients Suffering from Diffuse Hair Loss (Telogen Effluvium)

Abstract: The aim of the present study was to estimate the prevalence of telogen effl uvium (TE) and to evaluate the effi cacy of vitamin D in the treatment of this problem in women belonging to various cities of south Punjab, Pakistan. In the present study, 40 adult women suffering from the problem of TE were included. Each woman was treated with oral vitamin D 3 (200,000 IU) therapy fortnightly and a total of 6 doses were given to each patient. After 15 d of the last dose, the condition of patients was assessed clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…An additional survey on TE and treatment using search string 3 identified 11 papers (Table 1 ). 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 Currently, no established treatments or guidelines on TE treatment are available. 23 Various studies on treatment have been conducted.…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional survey on TE and treatment using search string 3 identified 11 papers (Table 1 ). 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 Currently, no established treatments or guidelines on TE treatment are available. 23 Various studies on treatment have been conducted.…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
“… 23 Various studies on treatment have been conducted. 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 The most common treatment was oral minoxidil (Table 3 ). 28 , 29 , 30 Literature reviews of 17 studies with 634 patients receiving oral minoxidil as the primary treatment for hair loss indicated that oral minoxidil was an effective and well‐tolerated primary medication to treat not only AGA but also other types of alopecia, including TE and AA with only minor adverse events.…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ruiz‐Tagle et al recommended a weekly dose of 50 000 IU of cholecalciferol for 1–3 months followed by a maintenance daily dose of 800–2000 IU to avoid recurrences 14 . Sattar et al supplemented oral vitamin D3‐200 000 IU fortnightly for 3 months in patients with TE, resulting in significant improvement in hair regrowth 15 …”
Section: Vitamin D In Telogen Effluviummentioning
confidence: 99%
“…14 Sattar et al supplemented oral vitamin D3-200 000 IU fortnightly for 3 months in patients with TE, resulting in significant improvement in hair regrowth. 15 Hence, it may be a prudent therapeutic strategy to measure vitamin D levels and supplement the same when deficient in patients of TE. 4,10,16 17 Zhao et al reported significant association between vitamin D levels and AA, FPHL, and male AGA.…”
Section: Vitamin D In Telog En Efflu Vi Ummentioning
confidence: 99%